Private security as moral drama: a tale of two scandals - Hansen Lofstrand, C; Loftus, B; Loader, I (Routledge, 2017)
This article explores the phenomenon of scandals as they unfold in the private security industry. We begin by outlining our theoretical understanding of scandals, before tracking the key phases of two recent events - one in Sweden, the other in Britain. Scandals, we suggest, are best viewed as moral tales which dramatize a host of societal norms and values about private security and criminal justice, prompting a great deal of normative conflict. The wider point we draw from the analysis is that when market actors enter the field of policing and criminal justice, they not only re-shape that field, they are also re-shaped by it. Private security cannot, in other words, escape the moral dilemmas and conflicts that inescapably attend practices of policing and punishment.